2018
DOI: 10.1002/app.46120
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a novel styrene copolymer: Simultaneously improving the thermal stability and toughness

Abstract: In order to improve the flame retardancy of polystyrene, a phosphorus-and nitrogen-containing monomer, N,N-tetramethyl-bis(phospohonate)-2-hydroxyethyl bis(methylene) amine acrylate (BC 2 NP 2 ), was synthesized and characterized, and then incorporated into various amounts of polystyrene via radical emulsion copolymerization. The copolymers prepared were characterized by Fourier transform infrared, nuclear magnetic resonance spectra, transmission electron microscopy, differential scanning calorimetry, thermalg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…3f, respectively (the particle size decreases with the increase of ammonium persulfate). The phenomenon indicates that the excessive anions S 2 O 4 2generated in the emulsion boosts the electrostatic repulsion between molecular groups, thereby, the stability of the nuclei is improved and the diameter of the products could be reduced [34]. Fig.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…3f, respectively (the particle size decreases with the increase of ammonium persulfate). The phenomenon indicates that the excessive anions S 2 O 4 2generated in the emulsion boosts the electrostatic repulsion between molecular groups, thereby, the stability of the nuclei is improved and the diameter of the products could be reduced [34]. Fig.…”
Section: Resultsmentioning
confidence: 96%
“…The diameter of the products increases from 0.8 μm to 2 μm with the promotion of the ratio of styrene and ammonium persulfate from 60: 1 to 100: 1. The phenomenon indicates that excessive styrene monomers could accelerate the growth of PS microspheres due to abundant nucleus for nucleating and extending [34].…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that when the content of DOPOAA in the copolymer increased, the Tg value of the copolymer decreased to 103 and 97 °C. This was because the introduction of DOPOAA made the copolymer obtain higher molecular flexibility [31,32], and DOPOAA had a significant effect on plasticizing the PS matrix.…”
Section: Characterization Of Dopoaa and Dopoaa-styrene Copolymermentioning
confidence: 99%
“…Compared with small molecule phosphorus-containing additive flame retardants, flame retardants that form an internal part structure show better stability and flame retardancy. Some phosphorus-containing flame-retardant monomers containing a C=C bond have been copolymerized with styrene to generate polymers with improved flame retardancy [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Introducing an elastomer to polymers or polymer blends has been the most effective and economical means for improving their impact toughness . However, elastomers exhibit poor toughening efficiency when IFR is introduced to polymers or polymer blendsElastomers should be distributed in the matrix or encapsulated in the polymer/IFR.…”
Section: Introductionmentioning
confidence: 99%